Truth, community, and the prophetic voice : Michael Walzer, Stanley Hauerwas, and Cornel West on justice and peace /: Michael Walzer, Stanley Hauerwas, and Cornel West on justice and peace. (2018) - Libby, Christopher J
No abstract available